To make the two expressions equivalent, we need to find the same exponent that can be applied to both expressions.
Using the power of a power property, (a^b)^c = a^(b*c), we can simplify the left side of the equation:
(3^3)^z = 3^(3*z)
So the equation becomes:
3^(3*z) = 3^24
Now, we can set the exponents equal to each other:
3*z = 24
Dividing both sides of the equation by 3:
z = 24/3
Simplifying the expression:
z = 8
Therefore, the exponent that would make the two expressions equivalent is z = 8.
What exponent would make the two expressions equivalent: (3^3)^z=3^24?
1 answer